KINERJA ATRIBUT KUALITAS BUAH LOKAL - Agriani Hermita Sadeli; Hesty Nurul Utami (Universitas Galuh, 2022)
Fruit supply in Indonesia comet from imports and locally. The number of fruit import increased from 2015 to 2020. Its a threat to local fruit agribusiness actors. Therefore, it is necessary to conduct research on the quality of local fruit so that it becomes input for agribusiness actors to increase their competitiveness. This research method is quantitative with survey technique. Data were obtained from the results of filling out questionnaires from 100 respondents who were found in traditional markets and modern markets in Jakarta. Data were processed using Importance-Performance Analysis. The results represent reshness is the most important quality attribute and taste is the attribute with the highest level of performance. Strategies need to be implemented by maintaining the quality of taste, freshness and vitamins, as well as improving appearance attributes and food safety. This can be done by making improvements starting from cultivation, harvesting and post-harvest so that food safety and the appearance of local fruit are imporved and maintained. Further research needs to be done by examining consumer satisfaction with local fruit.